Perbandingan Antara Nilai Indeks Variasi Gelombang Plethysmography dengan Nilai Variasi Tekanan Pulsasi Arteri pada Pasien dengan Ventilasi Tekanan Positif di ICU RSUP Dr. Sardjito - Bhaktiyar, Agung; Widodo, Untung; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Background: Pulse pressure variations (PPV) provide a good assessment of fluid status but require the installation of arterial line with high cost, difficult installation, and the risk of complications in the form of tissue death as well as infection. Meanwhile, the plethysmography variation index which has similarities to the pulse pressure variation that arises due to arteriolar pulses and is influenced by the breathing cycle, but is non-invasive, easy to apply, cheaper material, and without the risk of tissue death or infection. Methods: This study uses a prospective observational study design. We measured pulse pressure variation and plethysmography variability index (PVi) in 22 patients mechanically ventilated with preexisting radial artery catheter in intensive care unit (ICU). PPV was obtained by installing radial arterial line connected to Mostcare®. PVi was obtained by installing an oximetry probe on fourth finger and connected to the Masimo® monitor. We compared PPV and PVi using Mann-whitney test and looked for correlations with the spearman coefficient. Result: Twenty-two patients (SAPS II = 1.74 (0.4-75) had PPV values of 11.7 (7.03) and PVi 13.29 (7.76) different but were not statistically significant p = 0.405 (p> 0.05). There was a moderate correlation between PPV and PVi (r = 0.55). Four of the 22 patients receiving noreepinephiren (dose = 0.125 mcg / kg / min (0.1- 0.15)) showed no correlation between PPV and PVi (r = 0.40 p = 0.60). Conclusion: There was no significant difference between the value of the pulse pressure variation and the plethysmography variability index (PVi). There was a moderate correlation between the pulse pressure variation with the plethysmography variability index. There was no correlation between PVi and PPV in patients receiving norepinephrine.